2017
DOI: 10.1530/eje-16-0657
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in patients with diabetes mellitus and Addison’s disease: a nationwide, matched, observational cohort study

Abstract: Patients with the rare combination of diabetes and AD showed a markedly increased mortality and died more frequently from infections and unknown causes than patients with diabetes alone. Improved strategy for the management of this combination of metabolic disorders is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
(47 reference statements)
1
26
1
Order By: Relevance
“…Persons with endogenous Cushing's syndrome and/or any disorders of the pituitary gland were excluded. Details on all ICD-9 and ICD-10 codes used in this study are presented in previous article by our group (16). For T1DM, we used the clinical classification which is the diagnosis attributed to the persons by the physicians who reported them to the NDR.…”
Section: Reference Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…Persons with endogenous Cushing's syndrome and/or any disorders of the pituitary gland were excluded. Details on all ICD-9 and ICD-10 codes used in this study are presented in previous article by our group (16). For T1DM, we used the clinical classification which is the diagnosis attributed to the persons by the physicians who reported them to the NDR.…”
Section: Reference Locationmentioning
confidence: 99%
“…Previous studies have shown an increased risk of adrenal crises among persons with both T1DM and AD (16,26,27,28). Adrenal crisis is potentially lifethreatening if not discovered and treated in a timely manner.…”
Section: Persons With T1dmmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some of the non‐surgical cases are likely to be due to genetic mutations, for example, DiGeorge syndrome, which are known to be associated with congenital heart defects and urogenital abnormalities . Other autoimmune aetiologies, for example, autoimmune polyglandular syndrome, are associated with Addison's disease and thyroid disease potentially placing patients at risk . Conventionally, the aim of treatment has been to maintain the serum calcium concentration around the lower limit of the reference range.…”
Section: Introductionmentioning
confidence: 99%
“…13 Other autoimmune aetiologies, for example, autoimmune polyglandular syndrome, are associated with Addison's disease and thyroid disease potentially placing patients at risk. 14,15 Conventionally, the aim of treatment has been to maintain the serum calcium concentration around the lower limit of the reference range. This limits the risks of hypercalciuria and hypercalcaemia with the resultant risks of symptoms, renal stones and other complications.…”
mentioning
confidence: 99%